Udział Brunona Hussara OP w powstaniu dzieła św. Jakuba Apostoła - Tulej, Andrzej (Warszawskie Studia Teologiczne, 2024)
The article presents the influence, commitment, and participation of Bruno Hussar OP, a Dominican monk of Jewish origin who lived between 1911 and 1996, in the foundation of the Work of St. James the Apostle – Hebrew-speaking communities of the Latin Patriarchate of Jerusalem in the contemporary State of Israel. Hussar had a special predisposition that made up a kind of *casus singularis*, expressed in the self-definition that he felt "four identities" in himself. He was a Christian and a priest, a Jew, an Israeli, and, as he said, in a sense an Egyptian, because he was born and raised in Cairo in an Arab environment. Others referred to him as בעל חזון (*baal chazon*), a man of visions and dreams, simply a visionary. He was sent to Israel by his superiors with the mission of establishing a center for the study of Judaism. From the very beginning, he was faced with the problem of evangelization among the Jews and the realization of the so-called missionary mandate of Jesus: how does this command apply to Jews, with whom Christians have a special relationship? The first work in which Hussar participated and co-created was the Hebrew-speaking Church, later called the Work of St. James the Apostle. This community was born with difficulty, first searching for a place for the free, unfettered celebration of the Eucharist, and then seeking the possibility of using the Hebrew language in the liturgy. It was also important to anchor the Work institutionally within the local Church, which encountered numerous obstacles. Finally, the Work was approved by Patriarch Alberto Gori OFM on February 11, 1956.